Does expanding wood use in construction and textile markets contribute to climate change mitigation?. (March 2023) - Hurmekoski, Elias; Kunttu, Janni; Heinonen, Tero; Pukkala, Timo; Peltola, Heli
Abstract: Wood use is expanding to new markets, driven by the need to substitute fossil-intensive products and energy. Wood products can contribute to climate change mitigation, if they have a lower fossil footprint than alternative products serving the same function. However, the climate change mitigation potential is contingent on the net fossil and biogenic emissions over time, as well as the realism of the counterfactual scenario and market assumptions. This study aims to improve the consistency of assessing the avoided fossil emissions attributed to changes in wood use, and to estimate the additional mitigation potential of increased wood use in construction and textile markets based on wood harvested in Finland. The results show that, compared to baseline, an increase in the market share of wood leads to an increase in atmospheric CO2 concentration by 2050. Thus, the substitution impacts of wood use are not large enough to compensate for the reduction in forest carbon sinks in the short and medium term. This outcome is further aggravated, considering the decarbonization of the energy sector driven by the Paris Agreement, which lowers the fossil emissions of competing sectors more than those of the forest sector. The expected decarbonization is a highly desirable trend, but it will further lengthen the carbon parity period associated with an increase in wood harvest. This creates a strong motive to pursue shifts in wood uses instead of merely expanding all wood uses. Graphical abstract: Image 1 Highlights: Increase in wood use for construction or textiles increases net emissions by 2050 Substitution impacts will fall remarkably by 2050 due to decarbonization Results motivate shifts in wood uses as opposed to expanding all wood uses Substitution assumptions remain oversimplified which causes great uncertainty